Dynamical structure of Orion dwarf galaxy / Muhammad Musoddiq Jaafar - Jaafar, Muhammad Musoddiq (2011)
In this study, I focused on analysis of processes that shape galaxy evolution and how galaxy was form in canonically "simple" conditions is presented. The characteristics of Dwarf galaxies are also be determined. Dwarf galaxy is excellent laboratories for studying the birth of galaxy. Orion dwarf galaxy was discovered by Giovanelli in 1979. In 2008, other scientist was discovered HI and optical observations of the Orion dwarf galaxy. University of Rome Tor Vergata, Italy was proceeded the observation by using Very Large Array and obtain a several data. The distance from earth is about 5Mpc or 17.85 light years. The data were analysis and stimulated with the theory and equation to obtain the exact dynamical structure of Orion Dwarf Galaxy. It's included the analysis of a few parameters such as radius, rotation velocity, sigma, solar mass, luminosity and colour of the galaxy.